Persepsi Presenter Televisi di Sumatera Selatan terhadap Kehadiran Presenter Artificial Intelligence - Elliana .; Nuraida .; Jufrizal . (CV. ITTC INDONESIA, 2026)
This study aims to analyze the responses of television presenters in South Sumatra to the presence of Artificial Intelligence (AI), as well as the responses of local audiences. The aim is to determine the responses of presenters, producers, and audiences. The research location is PALTV and Sriwijaya TV, one of the television stations in South Sumatra, with two television producers, four presenters, and four audience members (journalism students from UIN Raden Fatah) as informants. This study uses a qualitative approach with a phenomenological method, involving in-depth interviews with presenters, local television producers, and audiences. Qualitative data analysis in this study was conducted through a process of data reduction, data compilation, and drawing conclusions. The theoretical framework used is the Diffusion of Innovation. The results show that the presence of AI presenters has a significant role transformation impact. Human presenters respond with anxiety regarding the potential for repetitive tasks (such as reading statistical data), but adaptively shift their focus to the advantages of soft skills. Professionally, AI serves as a trigger that forces human presenters to up-skill and strengthen their role as interpreters of in-depth content and emotional connectors. Local audience responses to AI are functional and conditional; They embrace AI for its information efficiency, but strongly resist its use in segments that require warmth, authenticity, and local dialect. The conclusion of this study is that television presenters in South Sumatra responded to the presence of AI presenters with both positive and negative responses, reflecting both anxiety and a drive to adapt. The majority of presenters expressed concerns about the future of the presence of AI presenters, but did not dwell on it; instead, they expressed a desire to continuously upgrade their skills to ensure human presenters remain relevant in the future.